Crushing analysis of hierarchical multicellular tubes with gradient character along axial and radial directions under oblique loads - Xiaolin Deng; Qi Lu; Fuyun Liu; Mei Liang; Qiuyun Wei; Jiale Huang (Heliyon, 2023)
To overcome the disadvantage of high initial peak crush force (IPCF) in hierarchical and gradient structures, the hierarchical multicellular tubes (HMTs) with gradient character along axial and radial directions are proposed based on the bidirectional structural characters of bamboo stem. Crashworthiness performances of HMTs under oblique loads are systematically studied by using numerical simulation. Results show that compared with the square tube with the same mass, HMTs have higher energy absorption capability under different impact angles. The maximum increases of specific energy absorption (SEA) and crush force efficiency (CFE) reach up to 67.02% and 806%, respectively. Whereas, the maximum decrease of IPCF reaches up to 79.92%. Effects of structural parameters, including hierarchical level, wall thickness and internode space, on the crashworthiness performances of HMTs are also fully investigated.